Hyper-fractionated radiotherapy as a bridging strategy to enhance CAR-T efficacy by regulating T-cell co-stimulatory molecules in relapsed/refractory diffuse large B-cell lymphoma - Jing Ruan; Daobin Zhou; Yan Zhang; Danqing Zhao; Chong Wei; Ke Hu; Fuquan Zhang; Xiaorong Hou; Wei Zhang (Frontiers in Immunology)
BackgroundBridging therapy can prevent patients from disease progression while waiting for CAR-T cell preparation. Hyper-fractionated radiotherapy can achieve an effective target dose within a short period, minimize radiation damage, and may modify immune environment compared to conventional radiotherapy.AimsThis study aims to investigate the efficacy and safety of bridging hyper-fractionated radiotherapy in combination with CAR-T therapy for relapsed/refractory diffuse large B-cell lymphoma. The potential mechanisms were explored.MethodsThis is a prospective pilot study. After T-cell collection, the patients underwent hyper-fractionated radiotherapy at lesion sites with 1.5 Gy twice daily for 10 days before CAR-T cell infusion. Peripheral blood immune cell subsets and quantitative serum proteomics were assessed before radiotherapy and after radiotherapy before CAR-T cell infusion.ResultsA total of 13 patients have been enrolled. The median follow-up time was 6 (3–24) months after CAR-T infusion. At 3-month follow-up, 9/13(69%) patients had CR, 1/13(8%) patient had PR, 1/13(8%) patient remained SD, and 2/13(15%) patients died of disease progression. The local recurrence rate was 1/13(8%). Seven patients have been followed up for more than 6 months, and they remain in CR. The median PFS and OS were not reached. No grade 3–4 CRS or ICANS were reported. After hyper-fractionated radiotherapy, peripheral PD1+CD8+T/T ratio significantly decreased while quantitative serum proteomics profiling showed a decrease in sCD28.ConclusionHyper-fractionated radiotherapy can rapidly control tumor progression sites without delaying the infusion time. This approach can improve the ORR and does not increase the incidence of CRS and ICANS. The mechanism may be related to the regulation of T-cell co-stimulatory molecules, which demands further exploration.